Pengelolaan Manajemen Dalam Mengurangi Resiko Pembiayaan Pada Bank Syariah - Sabrinasyah, Ajengesti Latifah; Febrianti, Rani (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2023)
Risk is a condition that exists in every business activity, including the banking business. Risk management is important for banks because it is related to the collection and distribution of customer funds, such as conventional banks and Islamic banks are not free from risk. The risks of Islamic banks are different from conventional banks due to the uniqueness of their products and financing agreements as well as the quality of human resources as risk managers. Managing risk management through risk identification, risk measurement, management policy and risk monitoring on character, capacity, capital, collateral and condition. This research is a field empirical research using a descriptive qualitative approach method with primary data collection techniques and secondary data. Risk managers socialize their products so that fund owners are interested in saving funds in banks based on agreed profit sharing, thus banks provide loans to parties who need funds based on their abilities, therefore the research aims to identify risks then find risk management solutions and develop ideal forms of legal protection inÂ reducingÂ risk.